2020
DOI: 10.1111/1744-9987.13473
|View full text |Cite
|
Sign up to set email alerts
|

Tunneled dialysis catheter exchange through fibrin sheath crevice vs in situ catheter exchange for the treatment of catheter dysfunction

Abstract: Our aim is to evaluate the safety and efficacy of tunneled dialysis catheter (TDC) exchange through fibrin sheath crevice vs in situ catheter exchange in hemodialysis patients with fibrin‐sheath‐related catheter dysfunction. Patients with fibrin‐sheath‐related catheter dysfunction who underwent TDC exchange in our center between 2012 January and 2017 December were retrospectively screened. The included patients were divided into the sheath‐crevice group (catheter was exchanged through fibrin sheath crevice) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…10 It could achieve durable catheter patency, 11 without increasing bacteremia rates. 12 Li et al 13 reported that catheter exchange through fibrin sheath crevice is an effective alternative strategy for in situ catheter exchange. This technique could achieve better 6-month maximum blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…10 It could achieve durable catheter patency, 11 without increasing bacteremia rates. 12 Li et al 13 reported that catheter exchange through fibrin sheath crevice is an effective alternative strategy for in situ catheter exchange. This technique could achieve better 6-month maximum blood flow.…”
Section: Discussionmentioning
confidence: 99%